2022
DOI: 10.3389/fgene.2022.907219
|View full text |Cite
|
Sign up to set email alerts
|

CircPUM1 Knockdown Confers Radiosensitivity in Oral Squamous Cell Carcinoma by Regulating the miR-580/STAT3 Pathway

Abstract: Background: CircPUM1 acts as an oncogene in a variety of tumors, and there is no related research on oral squamous cell carcinoma. This study aimed to evaluate the clinical significance of CircPUM1 in oral squamous cell carcinoma radiotherapy.Methods: Radio-resistant cell lines were established by increasing the X-ray dose. Analysis of CircPUM1 expression in oral squamous cell carcinoma was carried out using bioinformatics tools. Cell proliferation was analyzed with CCK-8 and colony formation. Protein and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“… 46 STAT3β, one of the spliced isoforms of (Signal Transducer and Activator of Transcription 3) STAT3, serving as a dominant‐negative regulator, enhances sensitivity to radiotherapy 47 but STAT3 itself attenuates the radiosensitivity on the contrary. 48 Our study found that the alternative splicing of FANCI would produce two isoforms, of which one was showed aggravating lung cancer cells’ radioresistance, whereas another had no effects. Previous studies and our study demonstrate that while taking measures for the prevention and treatment of radioresistance, it should be paid more attention to the effects of alternative splice, which might offer a new and challenging approach to reverse therapeutic resistance.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 46 STAT3β, one of the spliced isoforms of (Signal Transducer and Activator of Transcription 3) STAT3, serving as a dominant‐negative regulator, enhances sensitivity to radiotherapy 47 but STAT3 itself attenuates the radiosensitivity on the contrary. 48 Our study found that the alternative splicing of FANCI would produce two isoforms, of which one was showed aggravating lung cancer cells’ radioresistance, whereas another had no effects. Previous studies and our study demonstrate that while taking measures for the prevention and treatment of radioresistance, it should be paid more attention to the effects of alternative splice, which might offer a new and challenging approach to reverse therapeutic resistance.…”
Section: Discussionmentioning
confidence: 58%
“…Alternative splicing of coactivator‐associated arginine methyltransferase 1 (CARM1) by epithelial splicing regulatory protein 1 (ESRP1) resulted in lung cancer cells sensitize to chemotherapy 46 . STAT3β, one of the spliced isoforms of (Signal Transducer and Activator of Transcription 3) STAT3, serving as a dominant‐negative regulator, enhances sensitivity to radiotherapy 47 but STAT3 itself attenuates the radiosensitivity on the contrary 48 . Our study found that the alternative splicing of FANCI would produce two isoforms, of which one was showed aggravating lung cancer cells’ radioresistance, whereas another had no effects.…”
Section: Discussionmentioning
confidence: 99%
“…CCL4 enhances Angpt2 and VEGF-C expressions via the MEK/ERK/STAT3 and JAK2/STAT3 pathways, respectively, to promote angiogenesis and lymphangiogenesis in OSCC, thereby increasing the propensity of metastasis ( Lien et al, 2018 ; Lu et al, 2022 ). Additionally, STAT3 is associated with the chemosensitivity and radiosensitivity of OSCC cells ( Chen et al, 2019 ; Jia et al, 2022 ). Fewer studies have been conducted on the association between STAT1 and OSCC than on the role of STAT3 in OSCC.…”
Section: Discussionmentioning
confidence: 99%